(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
The study aims to reveal the role of management ethics in higher education institutions within the context of effective human resource management. The presence of ethical issues in higher education governance negatively affects both internal and external organizational processes. Management ethics in higher education institutions is not only a key factor in shaping academic culture but also a strategic resource that directly influences effective human resource management, the establishment of organizational culture, and the long-term sustainability of universities. The article presents the fundamental principles of management ethics, their application features, and their impact on the efficiency of higher education institutions. The research is based on an analysis of international and local scholarly sources, as well as empirical research, including the results of a sociological survey. The findings indicate that gaps in the management ethics system exacerbate issues related to transparency in university governance, fairness in personnel policies, and academic integrity. According to survey data, the main pathways to reducing ethical violations in educational institutions include revising ethical management standards, introducing monitoring mechanisms, and ensuring transparency in governance processes. The article analyzes different management styles (authoritarian, democratic, liberal, and mixed) and their influence on the formation of an ethical management environment. The key conclusions of the study confirm that clarifying ethical management standards, maintaining a consistent approach to moral values, and implementing effective monitoring systems can not only improve the internal functions of higher education institutions but also enhance public trust in them. Overall, strengthening management ethics should be considered a priority in higher education reforms, as ensuring the long-term stability, competitiveness, and high quality of education is impossible without a firm adherence to ethical principles.